Sarawak Social Welfare Dapartment / Nursharmina Lilek - Lilek, Nursharmina (University Technology MARA Sarawak, 2014)
Department of Social Welfare has been upgraded from the Welfare Division of the Ministry of Social Development Sarawak in March, 1993, the Department has evolved function and placed as a key agency under the Ministry of Social Development and Urbanization Sarawak. At its inception Welfare Division established to address the welfare of taking over Sarawak Welfare Council in providing General Assistance and help victims of the disaster, in addition to expanding charitable activities by providing support services required by the changing times.